Anthropogenic and natural risk factors of water supply in the Azovo-Dniprovskyi region - Hrebniak, N.P.; Fedorchenko, R.A.; Tulushev, Ye.A.; Chernenko, А.S. (Environment & Health, 2017)
Objective: We identified the anthropogenic and natural factors for the health of the population of the Azovsko-Dniprovskyi region due to the sources of drinking water supply.Materials and methods: Analysis of the sources of water supply was performed by the official reports. We used sanitary and analytical-and-synthetical methods.Results: Modern quality patterns of drinking water supply sources were determined by temporal and spatial features. Temporal patterns consist of the intensification of anthropogenic contamination of surface and underground water sources, the growth of qualitative and quantitative indices of drinking water contamination of chemical and microbiological nature, the violation of the ecological balance in the "air - water - soil" system, the emergence of new pathogens, especially for the population of risk groups (children, elderly, with chronic diseases, AIDS). Spatial patterns of the quality of drinking water sources are as follows: extremely poor quality of surface water basins of the 2-nd category by sanitary-and-chemical indices (59,1±3,8 %), high deviations from the hygienic standards in centralized water supply sources (22,6±4,5 %), mismatch of natural chemical composition of drinking water in the most of the administrative units of the oblast by the total mineralization (80,8 %) and stiffness (66,7 %), very low quality of water by sanitary-and-chemical indices in the sources of the rural taps (25,5±3,1 %).
Keywords: water supply sources; water quality; sanitary-and-chemical indices; microbiological indices